Solvothermal Development of Chitosan-Based Adsorbent for the Remediation of Nickel (II) Ions - Cahyo, Muhammad Fiqih Nur; Putri, Silvia Devi Eka; Dian, Saskia Eka; Aksaronas, Zidan Ashri; Thoriq, Anugrah; Adriansyah, Endi; Sufra, Rifqi; Setiawan, Ari (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Industrial processes that discharge heavy metals into the environment are a growing environmental crisis because of the dangers they pose to aquatic life and human health. Nickel (Ni) is one of the most dangerous metals due to its extreme toxicity and its ability to bioaccumulate in food chains. Severe health complications may develop from chronic exposure to nickel. Chemical precipitation, ion exchange, and reverse osmosis are traditional methods used to remove Ni(II) ions from wastewater. Nonetheless, these approaches have drawbacks, such as elevated operational costs, excessive chemical consumption, and inefficiency in treating low-concentration wastewater. The effectiveness of solvothermally synthesised chitosan as an adsorbent for the removal of Ni(II) ions from aqueous solutions was examined in this work. Acidity, adsorbent concentration, and contact duration were all carefully measured and analyzed. Optimal adsorption occurred at pH 6, yielding a maximum removal effectiveness of 75% after 75 minutes of contact. An adsorption efficiency of 54.69% was achieved with the optimal adsorbent dose of 0.4 g. Kinetic analysis indicated that the adsorption process followed the Pseudo-Second-Order (PSO) model, with a correlation coefficient (R²) of 0.999, suggesting that chemisorption prevailed via interactions between Ni(II) ions and the –NH? and –OH functional groups on the chitosan surface. The solvothermal modification improved the adsorption capability of the chitosan by increasing its surface area, porosity, and number of active sites. Contribution to Sustainable Development Goals (SDGs):SDG 6 – Clean Water and Sanitation (Wastewater Treatment)SDG 3 – Good Health and Well-being (Toxicity Reduction)SDG 12 – Responsible Consumption and Production (Eco-friendly Materials)SDG 14 – Life Below Water (Prevention of Bioaccumulation)